Intersectional innovation in biomarker development for patient-centric medicine. (July 2011) - Wilcoxen, Keith M; Hesterman, Jacob; Orcutt, Kelly Davis; Hoppin, Jack
The pharmaceutical and healthcare industries are being revolutionized by the use of genomics, proteomics, metabolomics, bioinformatics and molecular imaging. Patient friendly diagnosis, treatment and disease management options that utilize the combination of these technologies are currently in development. New innovations in pharmaceutical advancement are taking place at the intersection of these technologies, and will be coupled with societal changes as we move to a fully networked and individual-centric consumer base. Numerous examples of the combinations of molecular characterization technologies aimed at better preclinical and clinical disease understanding, diagnosis and treatment are highlighted that are ideally situated to generate the intersectional innovation that drives healthcare advancement. The true value in patient-centric medicine will only be realized as the improved molecular characterization of disease provided by these technologies is integrated across platforms that operate directly in the patient and care provider space to provide a comprehensive view of health. Molecular profiling and imaging technologies must become fully integrated and amenable for patient and physician use in a networked environment that can provide a personal health avatar approach to medicine.